(untitled) - Talukder, Assoke K. (New York, 2007)
The user in a mobile computing environment is able to access data from any device in a network while on the move, spread across wired and wireless media. The technology to deliver on this promise now exists, and is one of the key drivers for growth across the telecommunications industry. This book provides a detailed survery of the technologies delivering true mobile computing – on both the service creation and device fronts. This book guides communications professionals and students through the complex web of acronyms, standards that wireless data runs on. It also details hot button security issues and new emerging technologies.
Keywords: Mobile computing,Wireless communication systems